To solve this system of equations, we can add the two equations together to eliminate the variable y.
6x - 5y = 27
3x + 5y = 36
--------------
9x = 63
Dividing both sides by 9:
x = 7
Now that we have found the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the second equation:
3x + 5y = 36
3(7) + 5y = 36
21 + 5y = 36
5y = 15
y = 3
Therefore, the solution to the system of equations is x = 7 and y = 3.
Solve the system of equations.%0D%0A6x–5y=27%0D%0A3x+5y=36(1 point)%0D%0A(, )
1 answer